An irrigation experiment to compare soil, water and speleothem tetraether membrane lipid distributions. (April 2016) - Baker, Andy; Jex, Catherine N.; Rutlidge, Helen; Woltering, Martijn; Blyth, Alison J.; Andersen, Martin S.; Cuthbert, Mark O.; Marjo, Christopher E.; Markowska, Monika; Rau, Gabriel C.; Khan, Stuart J.
Highlights: Origin of GDGTs in speleothems is unknown. An irrigation experiment generated cave drip water for GDGT analysis. Drip water GDGTs distinct from soil and speleothem samples. Speleothem GDGTs probably have a subsurface source. Abstract: Measurement of glycerol dialkyl glycerol tetraethers (GDGTs) preserved in speleothems offers a potential proxy for past temperature but, in general, their origin is unknown. To understand the source of speleothem GDGTs, we undertook an irrigation experiment to activate drip sites within a hydrogeochemically well characterised cave. The cave drip water was analysed for GDGTs, inorganic elements (major ions and trace elements), stable isotopes and dissolved organic matter concentration and character. Published speleothem GDGT records from the site have been observed to be dominated by isoprenoid GDGTs and interpreted as deriving from in situ microbial communities within the cave or vadose zone. The drip water in our irrigation experiment had a GDGT distribution distinct from that of soil and speleothem samples, providing direct evidence that the distinctive GDGT signature in speleothems is derived from a subsurface source. Analysis of GDGTs in this context allowed further elucidation of their source and transport in cave systems, enhancing our understanding of how they might be used as a temperature proxy.